Natural lighting performance of vernacular architecture, case study oldtown Pasa, Ecuador - Bustán-Gaona, Darío (2023)
Vernacular architecture is an architectural style that reflects the traditions and cultural aspects of a particular region or community. It is characterized by the use of local materials and traditional construction techniques, adapting to the climatic, geographical, and cultural conditions of the place. Despite extensive research on the benefits of natural lighting in modern architecture, there is limited understanding of how vernacular architecture integrates natural lighting principles in various climatic conditions, mainly due to restrictions in intervention and concerns about structural integrity. In today's world, energy efficiency and conservation are crucial aspects of building design. Therefore, this study aims to analyze the effectiveness of natural lighting in the indoor spaces of vernacular architecture. The research includes measurements taken in traditional buildings in the parish of Pasa, Ambato, Ecuador, as well as simulations to evaluate the behavior of sunlight. The findings reveal that, with new construction technologies, lighting levels in the interior spaces of these buildings can be improved. To address this issue, a proposed solution is presented to optimize the use of natural light, resulting in an increase from 30 to 100 lx. This improvement could pave the way for the implementation of policies that enhance the quality of life for users.